Atasi Krisis Air Bagi Para Petani Padi Melaui Penyuluhan Kelompok Tani - Jalastu Fima Laya Rani; Solfema Solfema; Lili Dada Putri (Journal Innovation In Education, 2025)
The increasingly intensive water crisis threatens the sustainability of rice production, limited water resources are a serious problem for rice farming in the country. Various methods have been used, especially to increase raw water reserves, namely by building dams and reservoirs. However, this is still insufficient amidst the challenges of climate change in the current dry season. One effort to overcome this problem is through outreach to farmer groups. Through outreach, farmers are expected to be able to adopt efficient water management techniques, such as using water pumps, selecting drought-resistant rice varieties, and utilizing rainwater. This research aims to identify the obstacles faced by farmers in accessing and managing water, as well as evaluating the extent to which extension can provide effective solutions. It is hoped that the research results can provide policy recommendations to improve food security and farmer welfare amidst limited water resources.